STUDY ON PRETREATMENT OF NICKEL LATERITE ORE FOR MINERAL PROCESSING PROCESSES: REVIEW - Arya Purnama, Indirwan
Nickel is one of the widely used metal, this is because of the properties that it has such as high melting point (1453oC), not easy to corrode, and has the good toughness. Some of nickel application is in stainless steel industry, nickel based alloy, alloy steel, electroplating, and electronic battery. In nickel laterite ore processing with pyrometallurgical route or smelting, ore is drying prior to calcination, smelting, refining, and converting. This process needs higher nickel grade in the ore, higher than 1.5%. While 50% of nickel laterite reserve in the world has nickel grade lower than 1.45%. Because of that, research to enrich nickel grade on nickel laterite ore is important to learn. There was so many research that try to improve nickel grade in nickel laterite ore with conventional physical separation such as magnetic separation, gravity concentration, dense medium separation, and flotation. But the result of these process is not success to improve nickel grade significantly, especially low nickel recovery. In this study, the development of physical separation process in nickel laterite ore with pretreatment are reviewed. The pretreatment process is calcination, reduction, and sulphidation before the ore is concentrating in magnetic separation and flotation. The literature was collected first with keywords nickel laterite ore, calcination, reduction, sulphidation, magnetic concentration, and flotation. Each literature is being analyzed and the conclusion from each literature are drawn. The conclusion that must be drawn is about nickel grade and recovery. Parameter on thermal pretreatment such as temperature, duration, reductor, and additive addition is analyzed. Furthermore, the parameter in magnetic separation such as magnetic field strength and pulp density, and the parameter in flotation such as kind of collector and pH is analyzed. The conclusion from each literature are combined to produce a new conclusion that answer the objective of this research. The result show that the best result of all nickel laterite ore pretreatment were obtained in the reduction and magnetic separation process. The highest nickel grade, nickel recovery, and selectivity in reduction and magnetic separation process gives the best result compared with calcination and sulphidation pretreatment.